Christian hermeneutics in South Africa - Coetsee, Albert (Reformed Theology in Africa Series, 2022)
Hermeneutics remains a divisive and polarizing topic within scholarly and ecclesiastical communities in South Africa. These tensions are not limited to theoretical differences but often crystallize on a grassroots level when local churches and church assemblies have to make important decisions on controversial ethical topics such as ordaining women in church offices, assessing the ethics of gay marriages, and taking a stance on the land debate in South Africa. This book makes a unique contribution in two ways: firstly, it focuses on the uniquely South African hermeneutical landscape; secondly, it relates theories to practical ethical application. The unique scholarly contribution of this consists in it relating hermeneutics to ethics within the South African landscape. A diverse group of scholars have been invited to partake in the project and the views expressed are often quite diverse. This allows readers to develop an understanding and sensitivity of the various angles employed and the interests at stake in addressing difficult societal problems.